Analisis Green Marketing Mix Dalam Upaya Pengembangan Agrowisata Berbasis Masyarakat Di Desa Kluncing - Ahmadintya Anggit Hanggraito; Eka Afrida Ermawati; Inno Cahyaning Tyas (Forum Agribisnis, 2022)
In the global era, agricultural areas have become part of a new trend in the development of sustainable tourism in Indonesia. Branding of Kampoeng Ikan shows the great potential of the agricultural sector in sustainable tourism efforts in Klancing Village, Banyuwangi Regency. Therefore, community-based agrotourism is expected to be the right combination between rural communities and the agricultural sector in village development. The purpose of this study was to analyze the green marketing mix system and the role of the community as supporters in the agro-attraction development area in Klancing Village. Then, formulate an alternative strategy for developing community-based agro-tourism that is right for Klancing Village. This study uses descriptive research through a qualitative approach. The data analysis method uses an interactive analysis model that involves various stages in the community service program carried out from May to October 2021. The results of the analysis of the green marketing mix system and the role of the community are formulated in alternative community based agrotourism development strategies in Kluncing Village, namely, (1) Optimization of the master plan for the concept of community-based agro-tourism, (2) Socialization and Community Assistance related to environmentally friendly agricultural products, and (3) Optimization of existing social media. Through the green marketing mix approach, alternative village sustainable development strategies can have implications for eco-friendly tourism product management models and efficient village community empowerment.